Distance literacy in (and post) pandemic - Pinheiro, Petrilson (2020)
In this paper, I discuss the issue of literacy in the current context of the Covid-19 pandemic, in order to rethink education, in particular, the basic education, through a reflection that involves revisiting the past, critically analyzing the present and then imagining the future. I do a critical dialectical exercise, in which ideas are developed from theses, antitheses and syntheses, in an ambivalent way, trying to see tensions, contradictions and common dialogues, without deifying or demonizing possibilities. I conclude that it is necessary to establish guidelines for teachers that are feasible and flexible, especially in relation to the minimum technological infrastructure and the working conditions of teachers, respecting the reality of each context and the pedagogical proposals of each school. At this time, it is also essential that schools and teachers consider the diversity of students served, seeking to verify what resources students effectively must provide opportunities of learning for all.